Staffing Army ROTC at colleges and universities : alternatives for reducing the use of active-duty soldiers - Goldman, Charles A., 1964- (AD-a361 429., 1999)
The increased tempo and range of military operations, coupled with reduced manning levels, are exerting pressure on the Army to use its active-duty soldiers optimally. Consequently, the Army is seeking opportunities to fill positions now occupied by active-duty soldiers with other personnel. Specifically, a recent Armywide Institutional I TDA Redesign Study called for the design and testing of staffing alternatives for the Senior Reserve Officer Training Corps (SROTC) program using a combination of Active Component, Reserve Component, or former military personnel. In support of this requirement, RAND was asked to develop staffing alternatives and design a test of their effectiveness. This report discusses such alternatives and describes a test design to assess their feasibility for implementation throughout SROTC.